The effects of sports and physical activity on quality of life in elderly individuals taking regular medication - Yucel, Ali Serdar; Korkmaz, Murat; Abay, Perihan; Ozpinar, Saliha; Oztas, Dilek; Sevil, Umran; Kuyucu, Mihalis Michael (Campus Educa Sports Sl, 2025)
In this applied study, the effects of medication use and regular sports and physical activity on quality of life in elderly individuals who regularly use medication were examined. In this study, 4972 people with different demographic characteristics participated in this research and data were collected with a questionnaire method consisting of a 5-point Likert scale. The data obtained were in order to understand the effects of demographic variables on medication use and quality of life. Within the framework of the study, the relationship between demographic factors such as age, gender, educational status, marital status and medication use, medication recommendation and the number of medications used analysed in detail. After statistical analyses using ANOVA and Chi-square analyses, it found that medication use differed especially according to age and marital status, while medication recommendation was significantly related to gender, educational status and marital status. In terms of other findings, in addition to demographic factors, regular physical activity and sports positive effects on medication use. It was also determined that the number of medication used was significantly related to loneliness and feeling of helplessness. It also found that the feeling of loneliness and medication use pattern were in a significant relationship in individuals engaged in sports and physical activity. In addition, it was found that there was a significant relationship between medication intake and quality of life in individuals engaged in sports and physical activity. After this study, it has been revealed that it is a very important source to understand the relationship between medication use and quality of life in elderly individuals who do sports and physical activity and the importance of encouraging elderly individuals to do more physical activity.
Los efectos del deporte y la actividad física en la calidad de vida de los ancianos que toman medicación con regularidad
Keywords: elderly individuals; medication usage; sport and physical activity; quality of life; demographic variables